Investment : tutorial - Davydenko, Nadiia Mykolaivna; Kliuchka, Olha Volodymyrivna (NPE Yamchynskyi O.V., 2022)
The tutorial reveals the main provisions of investment theory and features of their implementation in practice. It examines the essence and main forms of investment, defines the conceptual principles of investment activities and the specifics of its implementation and financing by various entities. The tutorial considers methods for assessing the effectiveness of real and financial investments effectiveness and substantiates approaches to investment management. Each topic is accompanied by a list of questions for self-examination and tests for self-control. Some paragraphs include practical tasks that should enhance the independent work of students. There is a list of recommended literature for individual reading at the end of the tutorial. The tutorial is designed for students of economic specialties of higher education institutions, graduate students, teachers, scientists. The tutorial will also be useful for practitioners.

Підручник розкриває основні положення теорії інвестування та особливості їх реалізації на практиці. Розглядається сутність та основні форми інвестицій, визначаються концептуальні принципи інвестиційної діяльності та специфіка її здійснення і фінансування різними суб'єктами. У підручнику аналізуються методи оцінки ефективності реальних та фінансових інвестицій і обґрунтовуються підходи до інвестиційного управління. Кожна тема супроводжується списком питань для самоперевірки та тестами для самоконтролю. Деякі розділи включають практичні завдання, які мають на меті посилити самостійну роботу студентів. В кінці підручника надано список рекомендованої літератури для індивідуального читання. Підручник призначений для студентів економічних спеціальностей вищих навчальних закладів, аспірантів, викладачів, науковців. Також підручник буде корисним для практиків.
Keywords: investments; investment activity; performance assessment; investment management; real investments; financial investments; investment financing; investment methods; інвестиції; інвестиційна діяльність; оцінка ефективності; інвестиційне управління; реальні інвестиції; фінансові інвестиції; інвестиційне фінансування; методи інвестування